Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/07067437211037131
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Transitions, a Mental Health Literacy Intervention With Embedded Life Skills for Postsecondary Students: Preliminary Findings From a Naturalistic Cohort Study

Abstract: Objective Mental illness is a common medical condition to onset during adolescence. Young people who leave for postsecondary life are at an especially challenging period of lifetime when many will leave home and familiar environments for prolonged periods of time. These new circumstances may put young people at risk of developing mental health problems or disorders or exacerbate existing mental disorders. Alternatively, some young people may misinterpret the normal negative emotional states occurring as a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…These findings resonated with our research on a similar resource Transitions , designed for first-year postsecondary students. This research indicated students’ knowledge about postsecondary life improved and they would like to talk to others (e.g., friends, roommates, classmates, and parents) as a result of reading Transitions (Hunt et al, 2019; Kutcher et al, 2015a; Potvin-Boucher et al, 2010; Wei et al, 2022). This indicated that the MHL approach with embedded life skills may have the potential to support successful student transitions to postsecondary life as it includes comprehensive and rich information relevant to youth new life experiences.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These findings resonated with our research on a similar resource Transitions , designed for first-year postsecondary students. This research indicated students’ knowledge about postsecondary life improved and they would like to talk to others (e.g., friends, roommates, classmates, and parents) as a result of reading Transitions (Hunt et al, 2019; Kutcher et al, 2015a; Potvin-Boucher et al, 2010; Wei et al, 2022). This indicated that the MHL approach with embedded life skills may have the potential to support successful student transitions to postsecondary life as it includes comprehensive and rich information relevant to youth new life experiences.…”
Section: Discussionmentioning
confidence: 86%
“…Research demonstrated strong evidence to support that this resource improved youth understanding about mental health and reduced stigma against mental illness (Hunt et al, 2019; Kutcher et al, 2015a; Potvin-Boucher et al, 2010). Additionally, Transitions has been shown to benefit students by providing them with additional life skills strategies (e.g., budgeting, building relationships, developing identify, and maximizing learning) through independent reading, group discussions, and sessions led by trained peers, which helped to reduce perceived stress and therefore enhanced their resiliency (Wei et al, 2022). Transitions is the first of its kind to blend mental health with life skills that is supported by solid evidence in improving youth mental health in the postsecondary setting.…”
mentioning
confidence: 99%
“…Mental health knowledge was measured with a 30-item questionnaire based on the content of the Guide resource and required participants to choose from one of three options: ‘true,’ false’ or ‘do not know.’ Each correct answer received one point for a total possible score of 30. It is a well validated instrument addressing 5 topics; brain functions, basic facts about mental health and mental illness, information about specific mental disorders, consequences of untreated mental illness, and mental-illness treatments 30 .…”
Section: Methodsmentioning
confidence: 99%
“…Participants were then placed into one of four group's based on their baseline PSI score: “well”, “symptomatic”, “very symptomatic”, or “sick” (article citation). PSI group (well, symptomatic, very symptomatic, or sick), time point (baseline, follow-up 1, follow-up 2, and follow-up 3), and the interaction between PSI group and time were included as fixed effects, and participants as a random effect ( 48 ).…”
Section: Methodsmentioning
confidence: 99%